Sexual Violence Among Postsecondary Students: No Evidence that a Low Response Rate Biases Victimization or Perpetration Rates in a Well-Designed Climate Survey. Issue 5 (3rd September 2022) - Jeffrey, Nicole K.; Senn, Charlene Y.; Krieger, Michelle A.; Forrest, Anne
ABSTRACT: Purpose: The purpose of this study was to assess the accuracy and representativeness of common census-sampled campus climate surveys given the potential for misestimating sexual violence (SV) rates on campuses due to low response rates and self-selection bias in research (mixed findings in previous research). Method: We compared SV rates obtained from a census-sampled campus climate survey with a lottery draw (a common method for collecting campus SV data) with those obtained from a gender-stratified random sample survey with individual incentives. Results: We found no evidence that census-sampled campus climate surveys misestimate SV: our low response rate census-sampled survey produced very similar rates to our high response rate random sample survey. Discussion and Conclusion: Our research suggests that less costly and labor-intensive census-sampled surveys, when well-designed, produce sufficiently accurate and representative SV estimates on campuses despite their lower response rates.